When do elite speed skaters reach peak performance and how can it be enhanced? A longitudinal data study - Chen, Y.; Chen, J.; Chen, H.; Cao, Y.; Su, C.; Chen, L. (Research Square, 2024)
This study aimed to investigate the peak performance characteristics of world elite speed skaters and the key factors involved in the journey towards achieving better peak performance. Data from 651 elite skaters across the 2003/2004 to 2022/2023 seasons were collected from the International Skating Union database. Individual quadratic trajectories were used to track progression to peak performance. K means clustering grouped competitive feature variables, and key developmental factors were analyzed through a binary logistic regression model, with the Odds Ratio (OR) indicating whether a factor was favorable (OR>1) or unfavorable (OR<1). Significant differences (P<0.01) in the peak age between medalists and non-medalists were noticed, while no significant differences (P>0.05) were noticed between sexes or distances. Significant differences (P<0.05) were observed between genders, as well as between medalists and non-medalists in the peak-performance window. Binary logistic regression revealed that medium (OR=8.070) or high (OR=28.242) first participation performance, high first major competition performance (OR=4.818), medium (OR=10.661) or early (OR=51.592) first major competition age, medium career-best performance age (OR=40.333), participation frequency above 2.8 times/year in phase-3 (2.8-4.7 times/year: OR=5.132; 4.8-8.0 times/year: OR=8.171), and a career length of 9 years or more (9-13 years: OR=2.538; 14-21 years: OR=4.647) were favorable factors for achieving better peak performance. In conclusion, peak age range for world elite speed skates was 25-28 years, with a duration of peak performance lasting 4-5 year. Certain developmental factors were key conditions for world elite speed skaters to enhance their peak performance in the future.